Zedwulf: Power-Performance Tradeoffs of a 32-Node Zynq SoC Cluster - Moorthy, Pradeep (2015)
Commodity SoCs with hybrid architectures that combine CPUs with programmable FPGA fabric such as the Xilinx Zynq SoC have become a competitive energy-efficient platform for addressing irregular parallelism in graph problems. In this paper, we prototype a 32-node cluster composed from these Zynq SoC chips to accelerate communication-bound sparse graph-oriented applications such as neural network simulations. We develop specialized MPI routines specifically developed for irregular accelerator-to-accelerator communication of small message traffic. We use the ARM processor for handling the MPI stack while offloading compute-intensive calculations to the FPGA. For graphs with 32M nodes and 32M edges, Zedwulf delivers the highest 94 MTEPS (Million Traversed Edges Per Second)throughput over other x86 multi-threaded platforms in our study by 1.2 -- 1.4×. For this experiment, Zedwulf operates at an efficiency of 0.49 MTEPS/W when using ARM+FPGA which is1.2× better than using ARMv7 CPUs alone, and within 8% of the Intel Core i7-4770k platform.